(untitled) (Applied Biological Research, 2023)
The present study was conducted in a community pastureland of Spituk Monastery, Leh (Ladakh) from 2013 to 2015 to evaluate some temperate forage grasses/legumes and their mixtures grown in the interspaces of Salix plantation with a spacing of 4 m x 4 m. The experiment comprised of 13 treatments laid out in a randomized block design with each treatment replicated three times using a plot size of 12 m x 12 m. The results revealed that alfalfhad maximum value of sward height (62.5 cm), which was at par with treatment alfalfa grown in mixture with Dactylis tall fescue + sainfoin. However, plant cover was maximum (75.6-85.6%) in mixture treatments as compared to sole grass or legume treatments (20.4-80.6%). Maximum green (9.87 t ha-1) and dry fodder yield (2.68 t ha-1) was observed in Dactylis + tall fescue + sainfoin + alfalfa treatment, which was at par with tall fescue + alfalfa treatment. The mean values for plant height, collar diameter, diameter at breast height, number of branches and leaf yield were 1.79 m, 21.2 mm, 16.1 mm, 5.32 and 66.72 dry matter kg ha-1, respectively. The study suggests that tall fescue, Dactylis, red clover and sainfoin hold great promise as intercrop in Salix-based silvipastoral systems for der needs in the region.